Análisis de la introducción de la teoría de enlaces y bandas - Solbes, Jordi; Vilches, Amparo (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper analyses different approaches to the introduction of students to basic concepts of the chemical bond and band theories, as well as common misconceptions related to each concept.